Enhanced certificate revocation scheme with justification facility in mobile ad-hoc networks. Issue 97 (October 2020) - Krishnan, R. Santhana; Julie, E. Golden; Robinson, Y. Harold; Kumar, Raghvendra; Thong, Pham Huy; Son, Le Hoang
Abstract: MANETs cover immersed interests owing to their effortlessness in deployment and mobility. Dynamic environments make them defenceless to a variety of protection attacks while compared to static networks. The foremost confront is to assure safe transmission services in which certificate revocation is significant to protect unwanted activities in the network. This paper proposes an Enhanced Certificate Revocation Scheme with Justification Facility (ECRSJF) for certificate revocation to separate attackers from additional participation in network performance. In addition, to enhance the dependability of the methodology, we recuperate cautioned nodes to include in the certificate revocation procedure. To improve the correctness, we suggest a threshold-related method to evaluate and justify cautioned nodes as legal nodes. The overall performance of the ECRSJF scheme is evaluated by simulation. The performance results reveal that the certificate revocation scheme is successful and competent to protected communication in MANETs. The simulation results prove that our projected scheme provides the packet delivery ratio and revocation rate as 91% and 95% respectively. These results are better compared to those of the other existing schemes even in the presence of large number of attacker nodes.